2017
DOI: 10.5530/pj.2017.6s.165
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic Evaluation and Determination of Secondary Plant Metabolites by HPTLC and its Antioxidant Activity in Myrica esculenta

Abstract: Introduction:Myrica esculenta Buch.-Ham. (Myricaceae) is commonly known as Box Berry, Kaiphal, and Katphala in Ayurveda. As per the Ayurvedic literature the palnt is used for variety of diseases and disorders. Method: The present study deals with the pharmacognostical standardization, HPTLC analysis and antioxidant activity of methanolict extracts of the leaves of M. esculenta. The plant showed high phenolic and flavonoid content. In-vitro antioxidant study of dried leaves of Myrica esculanta was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Although the information on phenolic content and the antioxidant role of the fruit extract, juice, jam, and marc of M. rubra [24,25,26] is available, this information is lacking for M. esculenta . Earlier research reported the antimicrobial potential of M. esculenta fruit and bark [23,27,28,29], but still, no research has been carried out on the antimicrobial activity of its leaves. The possible differences in the composition and biological activities between extracts made by using different solvents on the extraction of plant natural products are well described [30].…”
Section: Introductionmentioning
confidence: 99%
“…Although the information on phenolic content and the antioxidant role of the fruit extract, juice, jam, and marc of M. rubra [24,25,26] is available, this information is lacking for M. esculenta . Earlier research reported the antimicrobial potential of M. esculenta fruit and bark [23,27,28,29], but still, no research has been carried out on the antimicrobial activity of its leaves. The possible differences in the composition and biological activities between extracts made by using different solvents on the extraction of plant natural products are well described [30].…”
Section: Introductionmentioning
confidence: 99%
“…The roots and leaves were dried under shade at room temperature. Dried roots and leaves of G. kurroo were finely grounded into a powder using an electrical grinder and stored in airtight containers at 4-8°C for further use (Kumar et al, 2017).…”
Section: Preparation Of Plant Extractmentioning
confidence: 99%
“…These solution mixtures were kept in the dark for 30 min, and the optical density was measured at 517 nm using a spectrophotometer against methanol. The control used was 3ml of methanol with 1ml of DPPH solution (0.004%) (Kumar et al, 2017;Bhuyar et al, 2021a, b). The DPPH radical scavenging ability of the sample was determined according to the following equation:…”
Section: Assay For Antioxidant Activitymentioning
confidence: 99%